Application of Talking Stick-Based Learning Media to Improve Students' Critical Thinking - Nabila Veronika; Muhammad Sadri; Zulham Siregar (research, training and philanthropy institution Natural Aceh, 2023)
The reason for this study is learners' low critical thinking ability on the material